CAT Systems in Foreign Language Teaching: Bridging Translation and Language Learning - Koshil, Nataliia (Педагогічна Академія: наукові записки, 2026)
This article examines the pedagogical potential of Computer-Assisted Translation (CAT) systems in foreign language teaching and highlights their role as an effective bridge between translation practice and language acquisition. In the context of rapid digitalization and the growing demand for technologically competent language professionals, CAT tools have become an integral component of modern language education. The study explores how the integration of CAT technologies transforms traditional approaches to foreign language instruction by combining linguistic analysis, translation strategies, and digital communication skills within a technology-enhanced learning environment. Special attention is devoted to the development of key competencies required for future translators and language specialists, including linguistic, communicative, intercultural, digital, and professional translation competencies. The article analyzes the educational functions of major CAT features, such as translation memory systems, terminology databases, concordance search, corpus alignment, and machine translation post-editing tools. These instruments facilitate more effective vocabulary acquisition, improve grammatical accuracy, and enhance discourse awareness by exposing learners to authentic multilingual contexts and repetitive language patterns. Furthermore, CAT environments encourage learner autonomy, collaborative learning, and active engagement with authentic translation tasks that simulate real professional situations. The research emphasizes that the use of CAT systems contributes to the formation of critical thinking, analytical abilities, problem-solving skills, and decision-making strategies, which are essential in both language learning and professional translation practice. Through interaction with digital translation platforms, students gain practical experience in managing terminology consistency, adapting texts to cultural contexts, and evaluating translation quality. The findings demonstrate that integrating CAT technologies into foreign language teaching modernizes the educational process and aligns it with contemporary standards of the global translation and communication industries. The article argues that CAT systems should be considered not merely as technical tools but as innovative pedagogical instruments that support a competency-based, learner-centered, and professionally oriented approach to language education.